Saamelaislasten ja -nuorten kulttuurioikeudet Suomessa, erityisesti kielen ja kulttuuri-identiteetin osalta - Joona, Tanja Leena (The Yearbook of Polar Law Online, 2018)
The article examines the common global phenomenon of indigenous urbanization. In Finland, more than 75 % of the indigenous Sámi children are born outside the Sámi Homeland area. The development is fast and poses different kind of challenges for the entire Sámi society and culture. Youth and women are more likely to settle in urban areas and it is their Sáminess that is to survive or die in the cities. Indigenousness is no longer tied with traditional livelihoods or land use but instead requires other forms of cultural maintenance. In the contemporary situation Sámi have started through their own associations and networks require more appropriate services in the cities, including Sámi language learning in the schools and kindergartens. This is not always satisfactory. The article evaluates the existing international and domestic (Finland) legislation in regard to Sámi language, but also the implementation of these rights in practice. The author would like to acknowledge that the article is based on a joint research project called NUORGÁV – An urban future for Sápmi?, between Norway, Sweden, Finland and Russia, where it is studied how Sámi youth organize and network to impact urban Sámi policy. The project is funded by the Research Council of Norway and administrated by Norwegian Institute for Urban and Regional Research (NIBR).